2022
DOI: 10.1073/pnas.2213986119
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs about minority representation in policing and support for diversification

Abstract: Diversification of police forces is widely promoted as a reform for reducing racial disparities in police–civilian interactions and increasing police legitimacy. Despite these potential benefits, nearly every municipal police department in the United States remains predominately White and male. Here, we investigate whether the scale and persistence of minority underrepresentation in policing might partly be explained by a lack of support for diversification among voters and current police officers. Across two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
13
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 57 publications
5
13
1
Order By: Relevance
“…Second, our findings contribute to a body of scholarship examining how message framing affects attitudes about police reform. We find that, unlike recent research (Novick & Pickett, 2022; Peyton et al, 2022; Vaughn et al, 2022), presenting factual information about policing does not affect policy preferences. In our study, participant attitudes about police reform were not affected when presented with statistics related to racial injustice nor those related to differential involvement in crime.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Second, our findings contribute to a body of scholarship examining how message framing affects attitudes about police reform. We find that, unlike recent research (Novick & Pickett, 2022; Peyton et al, 2022; Vaughn et al, 2022), presenting factual information about policing does not affect policy preferences. In our study, participant attitudes about police reform were not affected when presented with statistics related to racial injustice nor those related to differential involvement in crime.…”
Section: Discussioncontrasting
confidence: 99%
“…As such, researchers explored the impact of message framing on attitudes about police reform. One approach has been to present factual information about police shootings (Schiff et al, 2022) or police racial demographics (Peyton et al, 2022) to determine whether that information affects attitudes about reform. Peyton et al (2022) found that presenting participants with accurate information about police racial demographics increased support for hiring new officers from underrepresented groups.…”
Section: Framing and Public Opinionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that trust in the police can be enhanced through training to master dangerous situations without killing people and to hold police officers accountable for their deeds (Ehrenfeld & Harris, 2020) or through procedural justice training (Weisburd et al, 2022). Other measures include increasing officer diversity through hiring more women and people from underrepresented groups (Barnes et al, 2018;Peyton et al, 2022) as well as increased responsiveness (Van Craen & Skogan, 2015). Overall, positive and nonenforcement contact between the public and police are important to improve attitudes (Peyton et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The few experimental studies that exist found police diversity to be beneficial, although none focused on police-civilian encounters or civilians' reactions to specific officers. Peyton et al (2022) showed that when residents of Yonkers, New York, were informed about the low diversity among local police officers, it reduced their trust in policing. Riccucci et al (2018) found that Black Americans trusted a police department more when they were told 85 percent (compared with 15 percent) of its officers were Black.…”
Section: State Of the Evidence: Effects Of Police Diversitymentioning
confidence: 99%